Software complex for measuring operating systems’ main functions performance - Martyshkin, Alexey (Revista de la Universidad del Zulia, 2019)
This paper describes the software package created by the author for measuring the performance of operating system functions. This work aims to synthesize a software package designed to analyse the execution time of software functions of uniprocessor and multiprocessor operating systems. The package analyses a number of functions of operating systems: mutexes, semaphores, read-write locks, FIFO and PIPE channels, TCP and UDP sockets, context switching, system calls. Unlike analogues, this package is represented by a convenient graphical user interface; the Qt and Qwt libraries are used for its implementation, they have a rich set of widgets, i.e. programs that facilitate access to information. The libraries used are cross-platform, which allows us to make a simpler procedure for transferring applications to different operating systems; smoothing the test results curves is used. In conclusion, the results of test measurements are presented.